(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Before learning a foreign language, if the culture, values, and traditions of the people who speak that language are studied, it will be easier to understand the problems encountered in the process of learning the language. This article presents the rules for learning the Korean language correctly by examining the types and stylistic forms of address units, which are such a delicate point of the Korean language and Korean culture.